Antibody-based redirection of universal Fabrack-CAR T cells selectively kill antigen bearing tumor cells. Issue 6 (21st June 2022) - Kuo, Yi-Chiu; Kuo, Cheng-Fu; Jenkins, Kurt; Hung, Alfur Fu-Hsin; Chang, Wen-Chung; Park, Miso; Aguilar, Brenda; Starr, Renate; Hibbard, Jonathan; Brown, Christine; Williams, John C
Abstract : Background: Chimeric antigen receptor (CAR) T cells engineered to recognize and target tumor associated antigens have made a profound impact on the quality of life for many patients with cancer. However, tumor heterogeneity and intratumoral immune suppression reduce the efficacy of this approach, allowing for tumor cells devoid of the target antigen to seed disease recurrence. Here, we address the complexity of tumor heterogeneity by developing a universal CAR. Method: We constructed a universal Fabrack-CAR with an extracellular domain composed of the non-tumor targeted, cyclic, twelve residue meditope peptide that binds specifically to an engineered binding pocket within the Fab arm of monoclonal antibodies (mAbs). As this site is readily grafted onto therapeutic mAbs, the antigen specificity of these universal Fabrack-CAR T cells is simply conferred by administering mAbs with specificity to the heterogeneous tumor. Results: Using in vitro and in vivo studies with multiple meditope-engineered mAbs, we show the feasibility, specificity, and robustness of this approach. These studies demonstrate antigen- and antibody-specific T cell activation, proliferation, and IFNγ production, selective killing of target cells in a mixed population, and tumor regression in animal models. Conclusion: Collectively, these findings support the feasibility of this universal Fabrack-CAR T cell approach and provide the rationale for future clinical use in cancer immunotherapy.